Optimizing bioenergy and by-product outputs from durian shell pyrolysis. (February 2021) - Liu, Hui; Liu, Jingyong; Huang, Hongyi; Evrendilek, Fatih; Wen, Shaoting; Li, Weixin
Abstract: Durian shells (DS) constitute an abundant agricultural waste stream with a large yield in Southeast Asia and higher heating value. This study aimed to quantify the bioenergy and by-product outputs of the DS pyrolysis as a function of heating rate (5, 10, 20, and 40 K/min) combining thermogravimetric, Fourier transform infrared spectrometry, and pyrolysis–gas chromatography/mass spectrometry analyses. The joint optimizations of multiple responses were also performed as a function of a changing biofeedstock, heating rate, and temperature. The DS pyrolysis composed of three stages, with the main decomposition stage occurring between 141.2 and 616.5 °C. The increased heating rate promoted the DS pyrolysis, while the pyrolysis reaction was more complete at the low heating rate. Activation energy of the pyrolysis reaction was estimated to vary between 221.58 and 245.71 kJ/mol. The major gases evolved from the DS pyrolysis included CO2, CO, CH4, H2 O, carbonyl compounds, acids, and NH3 . The major pyrolytic by-products were aromatic and alicyclic hydrocarbons, phenolic substances, and N-containing compounds. Joint optimizations pointed to 999 °C, 5 K/min, and aboveground water hyacinth biomass, or DS as the most optimal operational conditions. Our findings provide insights into the optimization and scale-up for the industrial pyrolytic applications of DS. Graphical abstract: Image 1 Highlights: Bioenergy and by-products of durian shell (DS) pyrolysis were quantified. Changing biofeedstock, temperature and heating rate were jointly optimized. The activation energy of DS pyrolysis estimate varied between 221.58 and 245.71 kJ/mol. Aromatic hydrocarbon was the main bio-oils production of the DS pyrolysis. The comprehensive pyrolysis index ( CP1 ) of DS pyrolysis is between 0.0000491 and 0.0022268.